Changes in the role of explanatory factors for socioeconomic inequalities in physical performance: a comparative study of three birth cohorts - Silvia S. Klokgieters; Almar A. L. Kok; Marjolein Visser; Marjolein I. Broese van Groenou; Martijn Huisman (BMC, 2021)
Abstract Background Due to societal changes and changes in the availability of health promoting factors, explanatory factors of socioeconomic inequalities in health (SIH) may change with time. We investigate differences in the relative importance of behavioural, social and psychological factors for explaining inequalities in physical performance between three birth cohorts. Methods Data came from N = 988, N = 1002, and N = 1023 adults aged 55-64 years, collected in 1992, 2002 and 2012 as part of the Longitudinal Aging Study Amsterdam. Physical performance was measured by three performance tests. We included lifestyle factors (physical activity, smoking, alcohol use and Body Mass Index (BMI)); social factors (network size, network complexity, divorce, social support); and psychological factors (mastery, self-efficacy and neuroticism). In multi-group mediation models, we tested whether the strength of indirect effects from socioeconomic position (SEP) via the explanatory factors to health differed between birth cohorts. Stronger indirect effects indicate an increase in the importance; weaker indirect effects indicate a decrease in importance. Results Absolute SIH were present and similar across cohorts. The strength of indirect effects of SEP on physical performance through smoking, binge alcohol use, emotional support and mastery increased across cohorts. The indirect effects of BMI, network size, self-efficacy and neuroticism were similar across cohorts. Conclusions Inequalities in smoking, binge alcohol use, emotional support and mastery may have become more important for explaining SIH in recent cohorts of middle-aged adults. Policies that aim to reduce socioeconomic inequalities may need to adapt their targets of intervention to changing mechanisms in order to reduce SIH.